Plan estratégico para mejorar la gestión administrativa y contable de las empresas en el sector abarrotes mayorista-Eguren Trujillo 2012. - Ruiz Ochoa, César Ubaldo (2019)
ABSTRACT The purpose of this paper is a proposal for a Strategic Plan to Improve the Administrative and Accounting Management of Companies in the Grocery Sector in the Wholesale Market-Eguren Trujillo 2012. The problem investigated is: How a strategic plan will improve the administrative and accounting management of companies in the grocery sector in the wholesale market - Eguren Trujillo 2012 and the scenario is: If a Strategic Plan is proposed, it will contribute to the improvement of administrative and accounting management of companies in the grocery sector in the wholesale market- Eguren Trujillo 2012. The study population was the total of three hundred and twenty enterprises of the sector of groceries that make up the unit of analysis and the sample was the Nonprobabilistic sampling- By criterion of three companies. The method used was deductive, hypothesis and synthesis analysis and the techniques used were the survey where the most important and transcendental findings that were proposed in the Strategic Plan were compiled. In conclusion companies in the Wholesale Market Grocery Sector have a very changing environment, so administrative and accounting management do not manage a life plan for the company due to its lack of training, losing opportunities for growth. Therefore it is recommended to develop the Strategic Plan (proposed), where it allows them to have a vision, more projected according to their activities, looking for an improvement in the image and competitiveness.